The geostrategic implications of TTIP - Hamilton, Daniel S.; Blockmans, Steven (Brussels, 2015)
"The strategic considerations that define the perceived need for transatlantic renewal are the focus of this CEPS Special Report, in which the authors examine the geo-economic impact of the Transatlantic Trade and Investment Partnership (TTIP) on both emerging powers and poorer countries. Daniel Hamilton and Steven Blockmans argue that TTIP has the potential to be a catalyst for trade liberalisation at the global level, but only if the US and the EU are proactive about making the ‘open architecture’ of TTIP a reality."